2008
DOI: 10.1590/s0103-84782008000800036
|View full text |Cite
|
Sign up to set email alerts
|

Diferentes formulações de multimisturas sobre a resposta biológica em ratos

Abstract: Diferentes formulações de multimisturas sobre a resposta biológica em ratos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…10 A recent paper demonstrated that the use of the BD in growing Wistar rats caused a reduction in weight gain (25% lower) when compared to control rats fed the American Institute of Nutrition diet for growing rodents. 29 Nutritional deficiencies may increase Cd absorption and toxicity, which would render low-nutritional status populations particularly at risk for Cd exposure. 2,7 The reduction of feed intake, body weight gain, and feed efficiency ratio after exposure to 25 mg/kg Cd contrasts with previous studies, 18,20 where a similar Cd dose had no such effect.…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent paper demonstrated that the use of the BD in growing Wistar rats caused a reduction in weight gain (25% lower) when compared to control rats fed the American Institute of Nutrition diet for growing rodents. 29 Nutritional deficiencies may increase Cd absorption and toxicity, which would render low-nutritional status populations particularly at risk for Cd exposure. 2,7 The reduction of feed intake, body weight gain, and feed efficiency ratio after exposure to 25 mg/kg Cd contrasts with previous studies, 18,20 where a similar Cd dose had no such effect.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, o valor nutricional baixo, em termos de macronutrientes e micronutrientes, somado à presença de fatores anti-nutricionais, mostram a inadequação da multimistura como complemento nutricional. Corroborando com esta afirmação, Soares, Liberali e Fernandes Coutinho (2014), em uma revisão sistemática, concluíram que apesar de a multimistura possuir quantidades significativas de minerais e vitaminas e muitas fibras, muitas vezes, esses nem sempre estão disponíveis de acordo com que possam ser absorvidos pelo organismo, perante alguns fatores UNICIÊNCIAS, v. 23, n. 1, p. 38-42, 2019 por micro-organismos (MARQUES, 2012;MADRUGA et al, 2004, KAMINSKI, 2008MANTOVANI et al, 2008, DIAS et al, 2008, inclusive por micro-organismos indicadores de contaminação fecal, o que corrobora com os achados desse estudo. O laudo da análise de coliformes a 45 °C confirma a presença de Escherichia coli.…”
Section: Methodsunclassified
“…Resultados semelhantes foram obtidos por Gigante et al (2007), em que a suplementação com multimistura por seis meses não mostrou efeito significativo sobre nenhuma das medidas ou índices nutricionais estudados em crianças atendidas em escolas municipais de Educação Infantil. Estudos com animais têm mostrado os mesmos resultados insatisfatórios do impacto do produto na recuperação do estado nutricional (LEITE et al, 2002;MADRUGA et al, 2004;KAMINSKI et al, 2008).…”
Section: Conclusãounclassified